Post-pandemic psychosocial variables affecting academic dropout in a sample of Chilean higher-education students - Martínez-Líbano, Jonathan; Yeomans-Cabrera, María-Mercedes (Frontiers in Education, 2023)
Introduction: University dropouts are a problem in the Chilean higher education system, which causes psychosocial and economic damage and requires further studies to understand it comprehensively. This study aimed to determine the psychosocial variables influencing the risk of dropping out of the higher education system in a sample of Chilean university students post-pandemic. Methods: With a sample of 655 students from the Chilean higher education system and with a cross-sectional study design taken in November 2022, a questionnaire was applied with sociodemographic and other variables of interest, the Depression, Anxiety and Stress Scale DASS-2, the EAC-19 Coronavirus Affect Scale, the ECE Emotional Exhaustion Scale; the Okasha Suicide Scale, and the Insomnia Severity Index (ISI). We performed descriptive, bivariate, and multiple logistic regression analyses through SPSS version 25. Variables with a p-value < 0.05 in the final model were declared statistically significant. Odds ratios (OR) were adjusted to 95% confidence intervals (95% CI), which were used to determine the independent predictor variables. Results: Significant variables for the risk of dropping out of higher education were: failing four or more courses [AOR = 3.434; 95% CI: 1.272, 9.269], having depressive symptoms [AOR = 1.857; 95% CI: 1.214, 2.839], having suicidal ideation and thoughts [AOR = 2.169; 95% CI: 1.509, 3.118], having clinical insomnia [AOR = 2.024; 95% CI: 1.400, 2.927], low parental support [AOR = 1.459; 95% CI: 1.029, 2.069], impaired performance during the pandemic [AOR = 1.882; 95% CI: 1.317, 2.690], and impaired socioeconomic status during the pandemic [AOR = 1.649; 95% CI: 1.153, 2.357]. Conclusion: Chilean higher education institutions should pay attention to the risk factors resulting from this research, such as students with more than four failed courses during their career, depressive symptoms, suicidal thoughts, clinical insomnia, low parental support, and affectation in performance and socioeconomic level during the pandemic, which could contribute to improving academic retention indicators.